The Philippine civil service structure and policies - Dans, Albina M. (Philippine Journal of Public Administration, 1977)
The declaration of martial law in the country has facilitated the revamp of the civil service system via: (1) the promulgation of the Integrated Reorganization Plan which paved the way to restructure the civil service into a three-tiered sys. ter, rationalize the examination system, create a Career Executive Service, decentralize personnel functions, and categorize the service into career and non-career; and (2) the ratification of the 1973 Constitution which converted the Civil Service Commission to a three-man constitutional body. Other developments in public personnel administration are the: (1) coverage of government-owned and-controlled corporations under the Civil Service Law and Rules, (2) adoption of more facilitative personnel policies, (8) administrative discipline, and (4) human resources development. These changes have been made in order to have a progressive system of personnel administration and to promote morale, integrity, efficiency, and professionalism in the civil service.